Edge turbulence in ISTTOK: a multi-code fluid validation. (8th April 2021) - Dudson, B D; Gracias, W A; Jorge, R; Nielsen, A H; Olsen, J M B; Ricci, P; Silva, C; Tamain, P; Ciraolo, G; Fedorczak, N; Galassi, D; Madsen, J; et al.
Abstract: Fluid models used to study the edge plasma region need to be benchmarked against similar conditions given that models can strongly differ in complexity and therefore the results they produce. Via this validation study undertaken through the framework of EUROfusion Enabling Research, four state-of-the art models—GBS, Hermes/BOUT++, hot-edge-sol-electrostatic and TOKAM3X—are compared to experimental plasma turbulence measurements on the ISTTOK tokamak. Statistical comparisons of simulation and experiment data show that fluid models used here can replicate most of the experiment in terms of I sat and V float fluctuations despite their differences. Furthermore, it is shown that without including more complex information (like core turbulence information and domain geometry details and magnetic topological aspects) in fluid models, the results recovered vary from their experimental counterparts. Via the simulations using these codes, it is demonstrated that fluid models continue to be a good cost-effective tool in recovering many global aspects of edge plasma behaviour.